Magnetically Retrievable Modified Nickel Ferrite Nanoparticles: Efficient Catalytic Reduction of Nitroarenes and Photo-oxidation of Hazardous Dyes. Issue 2 (3rd March 2016) - Goyal, Ankita; Kapoor, Surbhi; Samuel, Pankaj; Singhal, Sonal
Abstract: Of recently, magnetic nano-ferrites have come forward as excellent catalysts for various organic transformations and mitigation of environmental deterioration. In the present investigation, attempts have been made to beneficially modify nickel ferrite nanoparticles by substituting various transition metal ions in to its lattice for catalytic applications. Synthesis of various modified nickel ferrite (NiM0.2 Fe1.8 O4 (M=Cr, Mn, Fe, Co, Ni, Cu and Zn) nanocatalysts have been carried out employing sol-gel methodology. Catalytic activity of the synthesized nanocatalysts have been evaluated both for the reduction of nitroaromatic compounds and for the deterioration of hazardous dyes. The catalytic performance of all the synthesized compositions have been found to follow the order- Mn > Cu > Co > Fe > Cr > Ni > Zn. The observed order of catalytic efficiency has also been confirmed from the completion time and rate constant values for both the catalytic reactions.